Design of a terminal node controller hardware for CubeSat tracking applications - Ahmad, Yasser Asrul; Nazim, NJ; Yuhaniz, SS (IOP, 2016)
CubeSats enable low-cost experiment and missions to be performed by universities and research institution in space. CubeSats for research are mainly using UHF and VHF communications for its tracking and telemetry applications. The current practice of a CubeSat communications is to modify radio amateur’s Terminal Node Controller (TNC) to enable data to be received in the ground station. The objective of this research is to design a hardware specifically used as a TNC for CubeSat tracking applications. A TNC is developed as an interface to the terminal and to serve as data packetization platform. The modem is integrated with a microcontroller unit (MCU) and an audio amplifier to enable in audio signals to be smoothened, amplified and interfaced with the radio. The modem, MCU, and audio amplifier circuitry are designed and integrated to form a TNC platform suitable for CubeSat communications.